UTILIZATION OF HIGH DEPENDENCY CARE BY GERIATRIC POPULATION IN A PRIVATE HOSPITAL IN MALAYSIA - Cheng Karmen; Choo Xin Hu; Ebenezer Esther Gunasel; Mohanty Basanta Kumar; Teo Cin Nee Dev (Asian Journal of Medicine & Health Sciences, 2019)
Background: The growth of aging population contributes to an increase utilization and burden on healthcare resources. Clinical assessment of geriatric patients admitted to High Dependency Unit (HDU) is essential to evaluate the level of care for benchmark setting of HDU admission criteria. The aim of the study was to assess the utilization of high dependency care by geriatric population in a private hospital in Malaysia. Methods: Every consecutive medical records of patients admitted to HDU of Ipoh Specialist Hospital (ISH) from 1st January 2016 to 30th June 2016 were collected from the Health Information Management System Services (HIMSS) and were recorded. The study variables were age, gender, ethnicity, length of stay, reasons for admission, sources of admission and co-morbidities. Bed occupancy rate and mortality rate at HDU were also calculated. Results: Total hospital admission to ISH in the first six months of 2016 was 12744, which included 572 admissions to a 13-bedded HDU. More than half (56.67%) of HDU admission within this period was contributed by geriatric population, out of which 56.04% were males. The bed occupancy rate of geriatric patients was 57.31%, which was consistently higher than the younger age group (39.86%) and the mean duration of HDU stay was 4.34 days ( 95% CI: 3.87-4.81). Admissions from the Accident and Emergency (A&E) department (p = 0.022) and medical causes (p = 0.000) were significantly higher in the geriatric age groups compared to the younger age group. Geriatric patients had significantly higher co-morbidities of ≥ 4 (p = 0.000). Conclusion: The HDU is most commonly utilized by geriatric population with multiple medical co-morbidities. The set up and the delivery of care in the HDU should be tailored towards the specific needs of elderly.